Pengaruh Ekologi Pertambangan Timah terhadap Sosial Politik Masyarakat di Pantai Batu Perahu Bangka Selatan - Deni Rumanti; Muhammad Prianda Putra Adibangsa; Nyimas Suci Kurniati; Bahjatul Murtasidin (Ideas Publishing, 2023)
The ecological influence of tin mining causes conflict for fishermen community followed by socio, economic and political factors. The research aims to reveal the potential conflicts which occur in tin mining conflicts between fishing communities and mines. The research uses descriptive qualitative methods. The results found that there are many factors occured, many actors who played in the conflict of tin mining and fishermen, as well as the tin mine itself which was indeed targeted and sought after by outsiders because they knew there is a lot of tin income in Batu Perahu Beach. The results of this research are expected to be used as literature and also as input for all communities and government circles.